4X+48=8(X+6)-4X

Simple and best practice solution for 4X+48=8(X+6)-4X equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4X+48=8(X+6)-4X equation:


Simplifying
4X + 48 = 8(X + 6) + -4X

Reorder the terms:
48 + 4X = 8(X + 6) + -4X

Reorder the terms:
48 + 4X = 8(6 + X) + -4X
48 + 4X = (6 * 8 + X * 8) + -4X
48 + 4X = (48 + 8X) + -4X

Combine like terms: 8X + -4X = 4X
48 + 4X = 48 + 4X

Add '-48' to each side of the equation.
48 + -48 + 4X = 48 + -48 + 4X

Combine like terms: 48 + -48 = 0
0 + 4X = 48 + -48 + 4X
4X = 48 + -48 + 4X

Combine like terms: 48 + -48 = 0
4X = 0 + 4X
4X = 4X

Add '-4X' to each side of the equation.
4X + -4X = 4X + -4X

Combine like terms: 4X + -4X = 0
0 = 4X + -4X

Combine like terms: 4X + -4X = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 252=4(-1-8v) | | -3-8p=-9p+6 | | 3a+3=9+a | | 4x-3(4-3x)=5(x-4)-40 | | Y/3=40 | | 17/6=34/x | | 2+3(x+5)=38 | | 154=7(7k+1) | | -4(n-6)=n+6 | | 5+8(x-3)=4-4(x-3) | | 4(3Z-1)-5(Z+4)=5(Z+1) | | 2/3=1/9(27) | | -27a-42=a+98 | | T/0.16=0.5/0.4 | | 110=7p-8(2-7p) | | 4(5x-4)=4x+17 | | -3-8=-9+6 | | 162=-6(1-7x) | | 19/11=q/15 | | C+212=-5c-28 | | 6s-8=1+5s | | 8(7n-4)=-480 | | 4x+3(x-9)=4(x-6) | | 7/13=n/11 | | 21x+y=9x+9y | | 133=-7(1+4m) | | 10-18(-10+4v)=99+19v | | 6+5c=3c | | N+-832=-24n+-7 | | 8(1-7n)=-328 | | M/7=-16 | | -6-11(p-2)=2(1-5p)-10 |

Equations solver categories